PD‐1 blockade enhances the antitumor efficacy of GM‐CSF surface‐modified bladder cancer stem cells vaccine. Issue 10 (26th December 2017) - Shi, Xiaojun; Zhang, Xinji; Li, Jinlong; Mo, Lijun; Zhao, Hongfan; Zhu, Yongtong; Hu, Zhiming; Gao, Jimin; Tan, Wanlong
Abstract : Eliminating cancer stem cells (CSCs) is a key issue in eradicating tumor. The streptavidin–granulocyte‐macrophage‐colony stimulating factor (SA–GM‐CSF) surface‐modified bladder CSCs vaccine previously developed using our protein–anchor technology could effectively induce specific immune response for eliminating CSCs. However, program death receptor‐1 (PD‐1)/program death ligand 1 (PD‐L1) signaling in tumor microenvironment results in tumor‐adaptive immune resistance. Although the CSCs vaccine could increase the number of CD8 + T cells, a part of these CD8 + T cells expressed PD‐1. Moreover, the CSCs vaccine upregulated the PD‐L1 expression of tumor cells, resulting in immune resistance. Adding PD‐1 blockade to the CSCs vaccine therapy increased the population of CD4 +, CD8 + and CD8 + IFN‐γ + but not CD4 + Foxp3 + T cells and induced the highest production of IFN‐γ. PD‐1 blockade could effectively enhance the functions of tumor‐specific T lymphocytes generated by the CSCs vaccine. This combination therapy improved the cure rate among mice and effectively protected the mice against a second CSCs cell challenge, but not a RM‐1 cell challenge. These results indicate that PD‐1 blockade combined with the GM‐CSF‐modified CSCs vaccine effectively induced a strong and specific antitumor immune response against bladder cancer. Abstract : What's new? Eliminating cancer stem cells (CSCs) is a key goal for eradicating tumors. Previously, the authors developed a SA‐GM‐CSF surface‐modified bladder cancer stem cells vaccine that effectively induced a specific immune response for eliminating CSCs. However, PD‐1/PD‐L1 signaling in the tumor microenvironment resulted in tumor adaptive immune resistance. This study demonstrates in a subcutaneous model of bladder cancer that PD‐1 blockade combined with the GM‐CSF‐modified MCSCs vaccine could induce better antitumor immunity than the vaccine or PD‐1 blockade alone can. The findings may provide an experimental basis for applying this type of combination therapy to the treatment of human bladder cancer.